School Principal’s Leadership and Teachers of English Professionalism - Azrielyani, Thadya; Mirizon, Soni; Vianty, Machdalena (Soegijapranata Catholic University, 2024)
Considering the great responsibility and the role of teachers as educators, teachers must have professional competence and determination to reach the projected educational goal. This competence should be developed continuously by the teachers themselves and/or facilitated by the principal as the leader in the school. Therefore, good leadership is required to guide and direct the teachers as should. The principal’s leadership quality can be seen in the success of the school he/she leads. This study examines the school principal’s leadership and English teachers’ professionalism at a private A-accredited high school in Palembang. A qualitative method in case study design was utilized in this study. A school principal, a vice-principal, and three teachers of English were involved as the participants of the study. The data were collected through interviews and observations and analyzed using thematic analysis. The findings of the study revealed that the school principal’s leadership plays a significant role in enhancing teachers’ English professionalism. The principal’s leadership styles are transformational and participative, which are characterized by vision articulation, inspirational motivation, intellectual stimulation, and individualized consideration. The study also found that teachers of English at this school are highly professional. They have a strong commitment to their teaching profession and are constantly striving to improve their teaching skills and knowledge.